2018
DOI: 10.2147/ijn.s159356
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically aligned fibrin nanofiber hydrogel accelerated axonal regrowth and locomotor function recovery in rat spinal cord injury

Abstract: BackgroundDesigning novel biomaterials that incorporate or mimic the functions of extracellular matrix to deliver precise regulatory signals for tissue regeneration is the focus of current intensive research efforts in tissue engineering and regenerative medicine.Methods and resultsTo mimic the natural environment of the spinal cord tissue, a three-dimensional hierarchically aligned fibrin hydrogel (AFG) with oriented topography and soft stiffness has been fabricated by electrospinning and a concurrent molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 47 publications
1
59
0
Order By: Relevance
“…As they lack an extracellular matrix and vascularization, cystic cavities do not promote regeneration of axons Hydrogels are biocompatible implants that have been used for creating a permissive environment, and bridging lesion cavities, by releasing neurotrophic substances. Yao et al 43 implanted an AFG hydrogel into a rat hemisected SCI model to bridge lesion cavities, which promoted axonal regeneration and locomotor function recovery of rats. Xu et al 44 demonstrated that FGF2loaded dscECM-HP hydrogel can achieve sustained release of FGF2 in vitro and recover both nerve tissue morphology and neuron functions in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…As they lack an extracellular matrix and vascularization, cystic cavities do not promote regeneration of axons Hydrogels are biocompatible implants that have been used for creating a permissive environment, and bridging lesion cavities, by releasing neurotrophic substances. Yao et al 43 implanted an AFG hydrogel into a rat hemisected SCI model to bridge lesion cavities, which promoted axonal regeneration and locomotor function recovery of rats. Xu et al 44 demonstrated that FGF2loaded dscECM-HP hydrogel can achieve sustained release of FGF2 in vitro and recover both nerve tissue morphology and neuron functions in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[66][67][68] Various 3D structures can be formed from the fibrin gel, in particular, by molding and electrospinning methods. 69,70 Moreover, the degradation rate of this hydrogel can be controlled locally, by, for example, the addition of fibrinolysis inhibitors. 71,72 Various modifications of the hydrogel can help in directing the differentiation of cells, in particular, in the angiogenic direction.…”
Section: Discussionmentioning
confidence: 99%
“…5,61,77,78 In addition, the ideal hydrogel product should be injectable and capable of filling any cavity defects specific to the fetus, thereby providing a scaffolding to bridge damaged axons within the spinal cord. 79 One drawback of fibrin hydrogels has been the rapid degradation by native plasmin over the first several weeks after application. 80,81 Although modifying the chemical properties of our hydrogels may extend its degradation until there is complete ingrowth of adjacent epithelium, another strategy to circumvent short degradation times would be to employ a biodegradable sheet on top of the hydrogel patch.…”
Section: Discussionmentioning
confidence: 99%